2020
DOI: 10.1007/s10853-020-04806-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes in CoCrFeMnNi under mild tribological load

Abstract: The lack of a principle element in high-entropy alloys (HEA) leads to unique and unexpected material properties. Tribological loading of metallic materials often results in deformed subsurface layers. As the microstructure feedbacks with friction forces, the microstructural evolution is highly dynamic and complex. The concept of HEAs promises high solid solution strengthening, which might decrease these microstructural changes. Here, we experimentally investigated the deformation behavior of CoCrFeMnNi in a dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…So, the result indicated that the transition occurred from adhesive and abrasive wear to delamination as the duration of wear is continued and examined the variation of CoF with load, sliding speed, and time [175]. Dollmann et al [176] investigated the wear behaviour of CoCrFeMnNi HEAs in a separate study. A soft fcc HEA has a low hardness value for the undeformed surface, while the hardness value increases significantly to 500 HV for the deformed surface.…”
Section: Tribological Characteristicsmentioning
confidence: 99%
“…So, the result indicated that the transition occurred from adhesive and abrasive wear to delamination as the duration of wear is continued and examined the variation of CoF with load, sliding speed, and time [175]. Dollmann et al [176] investigated the wear behaviour of CoCrFeMnNi HEAs in a separate study. A soft fcc HEA has a low hardness value for the undeformed surface, while the hardness value increases significantly to 500 HV for the deformed surface.…”
Section: Tribological Characteristicsmentioning
confidence: 99%
“…Other sophisticated routes exist for imparting higher strength to metals, and providing thermal stability to the underlying microstructural features, like grain boundaries and dislocations. Some relatively recent examples include the formation of thick boundaries (sometimes called complexions) [253][254][255], solution strengthening [46,81] in high entropy alloys [256][257][258][259][260][261][262][263] (where combinations of multiple elements increases the energy required for dislocation motion), and metastable amorphous bulk metallic glasses [264][265][266][267].…”
Section: Routes For Promoting Grain Boundary Sliding In Metalsmentioning
confidence: 99%
“…In turn, the resulting deformation layer leads to a change in the friction coefficient. So far, various microstructural characteristics have been observed in coarse grained, face-centred cubic (fcc) metallic materials under tribological load, such as a dislocation trace line [4,5], subgrain formation [2,6], deformation twinning [7,8], band-like patterns [9][10][11] and nanocrystalline grains [7,12].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The two normal loads they applied resulted in different grain sizes in the subsurface area [12]. In our earlier work, we analysed the microstructural evolution with increasing cycle number with a focus on the onset of microstructural changes at high friction coefficients [7]. In contrast, the influence of the friction and normal force is investigated after a single-trace experiment in this manuscript.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation